2019
DOI: 10.1186/s12941-019-0319-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter study on the evaluation of antimicrobial resistance and molecular epidemiology of multidrug-resistant Acinetobacter baumannii infections in intensive care units with clinical and environmental features

Abstract: Background Multidrug-resistant (MDR) Acinetobacter baumannii infections are considered as emerging nosocomial infections particularly in patients hospitalized in intensive care units (ICUs). Therefore, reliable detection of MDR strains is crucial for management of treatment but also for epidemiological data collections. The purpose of this study was to compare antimicrobial resistance and the clonal distribution of MDR clinical and environmental A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 22 publications
5
38
3
5
Order By: Relevance
“…These results were in contrast with those of Boral et al. [ 36 ] and Cheikh et al. [ 42 ] who reported that none of the A. baumannii isolates contained the bla oxa-48 gene.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results were in contrast with those of Boral et al. [ 36 ] and Cheikh et al. [ 42 ] who reported that none of the A. baumannii isolates contained the bla oxa-48 gene.…”
Section: Discussioncontrasting
confidence: 99%
“…Acinetobacter baumannii strains had a high level of resistance to all tested antibiotics, the results of which are in agreement with those obtained by Boral et al. [ 36 ], Azimi et al. [ 1 ], Romanin et al.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Boral et al [26], antibiotic resistance for Ciprofloxacin, Imipenem, Ampicillin/sulbactam, Ceftazidime, and Amikacin was observed to be 100%, 99.4%, 99.4%, 99.4%, and 91.8%, respectively. That is an increase in reported antibiotic resistance compared to the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Bu çalışmaya, Türkiye'nin farklı coğrafik bölgelerinde yer alan toplam 10 merkezden elde edilen ÇİD oldukları ve benzerlik durumları PFGE yöntemiyle daha önceden belirlenmiş invaziv A.baumannii izolatları (n= 156) dahil edildi 8 . Bu izolatlar kan, beyin omurilik sıvısı (BOS) ve özellikle cerrahi yoğun bakım ünitelerinde enfeksiyon tanısı ile tedavi edilen hastaların invaziv örneklerinden elde edildi.…”
Section: Bakteri İzolatlarıunclassified